Production of pectate lyase by penicillium viridicatum RFC3 in solid-state and submerged fermentation - Ferreira, Viviani [UNESP]; Da Silva, Roberto [UNESP]; Silva, Dênis [UNESP]; Gomes, Eleni [UNESP] (Wiley, 2010)
Pectate lyase (PL) was produced by the filamentous fungus Penicillium viridicatum RFC3 in solid-state cultures of a mixture of orange bagasse and wheat bran (1 : 1 w/w), or orange bagasse, wheat bran and sugarcane bagasse (1 : 1 : 0.5 w/w), and in a submerged liquid culture with orange bagasse and wheat bran (3%) as the carbon source. PL production was highest (1,500U mL -1 or 300Ug -1 of substrate) in solid-state fermentation (SSF) on wheat bran and orange bagasse at 96 hours. PL production in submerged fermentation (SmF) was influenced by the initial pH of the medium. With the initial pH adjusted to 4.5, 5.0, and 5.5, the peak activity was observed after 72, 48, and 24 hours of fermentation, respectively, when the pH of the medium reached the value 5.0. PL from SSF and SmF were loaded on Sephadex-G75 columns and six activity peaks were obtained from crude enzyme fromSSF and designated PL I, II, III, IV, V, andVI, while five peaks were obtained fromcrude enzyme fromSmF and labeled PL I', II', III', IV', and VII'. Crude enzyme and fraction III from each fermentative process were tested further. The optimum pH for crude PL from either process was 5.5, while that for PL III was 8.0. The maximum activity of enzymes from SSF was observed at 35°C, but crude enzyme was more thermotolerant than PL III, maintaining its maximum activity up to 45°C. Crude enzyme from SmF and PL III' showed thermophilic profiles of activity, with maximum activity at 60 and 55°C, respectively. In the absence of substrate, the crude enzyme from SSF was stable over the pH range 3.0-10.0 and PL III was most stable in the pH range 4.0-7.0. Crude enzyme from SmF retained 70%-80% of its maximum activity in the acid-neutral pH range (4.0-7.0), but PIII showed high stability at alkaline pH (7.5-9.5). PL from SSF was more thermolabile than that from SmF. The latter maintained 60% of its initial activity after 1 h at 55°C. The differing behavior of the enzymes with respect to pH and temperature suggests that they are different isozymes. Copyright © 2010 Viviani Ferreira et al.
Keywords: Fungi; Penicillium; Penicillium viridicatum; Triticum aestivum